Management of human behavior in organizations - Martires, Concepcion Rodil; Fule, Galileo S. (Mandaluyong City, Philippines : National Book Store, 2000)
This book is concerned with excellence and deliberately making it happen in organizations. As, such it deals quite extensively with many aspects of human behavior in organizations.
Part 1. Motivation -- Part 2. Management.
Includes bibliographical references and index.
Keywords: PERSONNEL MANAGEMENT